The Patient-Reported Outcomes Thermometer–5-Item Scale (5T-PROs): Validation of a New Tool for the Quick Assessment of Overall Health Status in Painful Rheumatic Diseases - Fausto Salaffi; Marco Di Carlo; Marina Carotti; Sonia Farah (Pain Research and Management)
Objective. To investigate the construct validity, reliability (internal consistency and retest reliability), and feasibility of the patient-reported outcomes thermometer–5-item scale (5T-PROs), a new tool to measure overall health status in patients with painful chronic rheumatic diseases such as rheumatoid arthritis (RA), psoriatic arthritis (PsA), axial spondyloarthritis (axialSpA), and fibromyalgia (FM). Methods. Consecutive patients have been involved in this study. The following analyses were performed to establish the validity of the 5T-PROs: (1) principal component factor analysis was used to identify the presence of a relatively small number of underlying latent factors than can be used to represent relations among sets of many variables; (2) Cronbach’s alpha was calculated as an indicator of internal consistency; and (3) Pearson product-moment correlations were conducted to assess the convergent validity. The 5T-PROs was also administered a second time (two weeks after the initial administration) to a subset of sample (n = 426) to allow for calculation of test-retest reliability. We used the intraclass correlation coefficient (ICC) as an estimate of test-retest reliability. Additionally, discriminant validity was tested using analysis of variance (ANOVA) with Bonferroni post hoc multiple comparisons, in different disease conditions. Feasibility was analyzed by the time taken in completing the 5T-PROs and the proportion of patients able to complete the 5 item. Results. 1,199 patients (572 with RA, 251 with axialSpA, 150 with PsA, and 226 with FM) were examined. The mean age was 55.7 (standard deviation: 13.1; range: 20 to 80) years. Factor analysis yielded two factors which accounted for 62.54% of the variance of the 5T-PROs. The first factor “Symptom Summary Score” (35.57% of the variance) revealed a good internal consistency (alpha = 0.88); the internal consistency of the second factor “Psychological Summary Score” (26.97% of the variance) was moderate (alpha = 0.69). The reliability of the whole instrument was good (alpha = 0.82). A very high correlation was obtained between Symptom Summary Score and SF-36 PCS and between pain thermometer intensity and SF-36 bodily pain. For all five items and summary scale scores of the SF-36, there was strong evidence that the mean rank of the scores differs significantly between the groups (Kruskal–Wallis tests, p<0.001). Discriminant validity, assessed by comparing the 5T-PRO dimensions in patients with different states of disease activity, showed that the 5T-PROs show moderate association with the presence of comorbidities. It was also noted that it was inversely correlated (p=0.01) to years of formal education. Conclusion. The 5T-PROs is easily administered, reliable and a valid instrument for evaluating the extensive multidimensional impact associated with chronic painful rheumatic conditions.